Neuroprotection is improved by watertightness of fetal spina bifida repair in the sheep model. (3rd January 2023) - Joyeux, L.; van der Merwe, J.; Aertsen, M.; Patel, P. A.; Khatoun, A.; Mori da Cunha, M. G. M. C.; De Vleeschauwer, S.; Parra, J.; Danzer, E.; McLaughlin, M.; Stoyanov, D.; Vercauteren, T.; et al.
ABSTRACT: Objectives: A contributing factor to unsuccessful prenatal spina bifida aperta (SBA) repair via an open approach may be incomplete neurosurgical repair causing persistent in‐utero leakage of cerebrospinal fluid (CSF) and exposure of the fetal spinal cord to amniotic fluid. We aimed to investigate the neurostructural and neurofunctional efficacy of watertight prenatal SBA repair in a validated SBA fetal lamb model. Methods: A well‐powered superiority study was conducted in the validated SBA fetal lamb model ( n = 7 per group). The outcomes of lambs which underwent watertight or non‐watertight multilayer repair through an open approach were compared to those of unrepaired SBA lambs (historical controls) at delivery (term = 145 days). At ∼75 days, fetal lambs underwent standardized induction of lumbar SBA. At ∼100 days, they were assigned to an either watertight or non‐watertight layered repair group based on an intraoperative watertightness test using subcutaneous fluorescein injection. At 1–2 days postnatally, as primary outcome, we assessed reversal of hindbrain herniation using magnetic resonance imaging (MRI). Secondary proxies of neuroprotection were: absence of CSF leakage at the repair site; hindlimb motor function based on joint‐movement score, locomotor grade and Motor Evoked Potential (MEP); four‐score neuroprotection scale, encompassing live birth, complete hindbrain herniation reversal, absence of CSF leakage and joint‐movement score ≥ 9/15; and brain and spinal cord histology and immunohistochemistry. As the watertightness test cannot be used clinically due to its invasiveness, we developed a potential surrogate intraoperative three‐score skin‐repair‐quality scale based on visual assessment of the quality of the skin repair (suture inter‐run distance ≤ 3 mm, absence of tear and absence of ischemia), with high quality defined by a score ≥ 2/3 and low quality by a score < 2/3, and assessed its relationship with improved outcome. Results: Compared with unrepaired lambs, lambs with watertight repair achieved a high level of neuroprotection (neuroprotection score of 4/4 in 5/7 vs 0/7 lambs) as evidenced by: a significant 100% ( vs 14%) reversal of hindbrain herniation on MRI; low CSF leakage (14% vs 100%); better hindlimb motor function, with higher joint‐movement score, locomotor grade and MEP area under the curve and peak‐to‐peak amplitude; higher neuronal density in the hippocampus and corpus callosum; and higher reactive astrogliosis at the SBA lesion epicenter. Conversely, lambs with non‐watertight SBA repair did not achieve the same level of neuroprotection (score of 4/4 in 1/7 lambs) compared with unrepaired lambs, with: a non‐significant 86% (vs 14%) reversal of hindbrain herniation; high CSF leakage (43% vs 100%); no improvement in motor function; low brain neuron count in both the hippocampus and corpus callosum; and small spinal astroglial cell area at the epicenter. Both watertight layered repair and high (≥ 2/3) intraoperative skin‐repair‐quality score were associated with improved outcome, but the watertightness test and skin‐repair‐quality scale could not be used interchangeably due to result discrepancies. Conclusions: Watertight layered fetal SBA repair is neuroprotective since it improves brain and spinal‐cord structure and function in the fetal lamb model. This translational research has important clinical implications. A neurosurgical technique that achieves watertightness should be adopted in all fetal centers to improve neuroprotection. Future clinical studies could assess whether a high skin‐repair‐quality score (≥ 2/3) correlates with neuroprotection. © 2022 International Society of Ultrasound in Obstetrics and Gynecology.